(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article deals with the possibilities of content-analysis of the literary works on the base of the gender problem; the aspects of research, the type of extract which may be used for this type has been defined; we explained the peculiarites of this type usage in the description of the attributes of men’s and women’s communication process.